(untitled) (Journal of Global Arts Studies, 2024)
Background ：The new National Central Museum of Korea has achieved comprehensive practical results in the construction of its navigation system since its opening in 2005. Purpose：To sort out and analyze the design of the navigation system of the museum, and explore the development trend of the navigation system design in the nearly twenty years after the establishment of the new museum. Methods：Based on literature research, practical research, and on-site observation, collect, experience, and analyze the navigation methods involved in the museum. Results： It was summarized that the museum’s development trend is towards diversified navigation experiences. Based on the current development status, its navigation methods are divided into three types: online navigation, offline navigation, and accessible navigation for analysis. Summarize the advantages and disadvantages of the current design of the navigation system in the museum. Conclusion：Starting from the perspective of user experience, we aim to find and solve practical problems, and explore and prospect future development trends and paths. To further improve the construction of a diversified navigation system and provide a more comprehensive navigation service system for the National Central Museum of Korea.